2003
DOI: 10.1017/s0022112002003646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deceleration on jet instability

Abstract: A non-parallel analysis of time-oscillatory instability of conical jets reveals important features not found in prior studies. Flow deceleration significantly enhances the shearlayer instability for both swirl-free and swirling jets. In swirl-free jets, flow deceleration causes the axisymmetric instability (absent in the parallel approximation). The critical Reynolds number Re a for this instability is an order of magnitude smaller than the critical Re a predicted before for the helical instability (where Re a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The shear layer instability seems to peak during the flow deceleration stage and this suggests that flow deceleration might be an important factor in these jets. It should be noted that Stern and Hussain (2003), who conducted a study of the flow instability of a conical jet, showed that jet instability is greatly enhanced by the flow deceleration. Once the jet is destabilized, the asymmetric vortices interact with each other and with the wall.…”
Section: B Vortex Dynamics Of Symmetry Breaking and Agjdmentioning
confidence: 99%
See 1 more Smart Citation
“…The shear layer instability seems to peak during the flow deceleration stage and this suggests that flow deceleration might be an important factor in these jets. It should be noted that Stern and Hussain (2003), who conducted a study of the flow instability of a conical jet, showed that jet instability is greatly enhanced by the flow deceleration. Once the jet is destabilized, the asymmetric vortices interact with each other and with the wall.…”
Section: B Vortex Dynamics Of Symmetry Breaking and Agjdmentioning
confidence: 99%
“…Second, during stages in the cycle when the jet velocity is low (early opening or late closing stages), even small velocity fluctuations in the surrounding flow can potentially produce large perturbation in the jet. Third, decelerating shear layers are inherently unstable (Stern and Hussain, 2003) and these can cause or enhance asymmetries in the glottal jet. Despite this, many studies, especially the earlier ones (Berg et al, 1957;Guo and Scherer, 1994;Scherer et al, 2001;Fulcher et al, 2006), did not include jet pulsatility in their models.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that Shtern & Hussain (2003) found similar instabilities for conical jets. They showed via a non-parallel analysis that flow deceleration plays a major role for swirl-free jets, triggering non-axisymmetric instabilities.…”
Section: Symmetry-breaking Bifurcation In the Symmetric Expansionmentioning
confidence: 53%
“…For more details concerning the stability problem and the numerical technique, see Ref. 7. Figures 2 and 3 show the summarized results of our stability studies for the flows in conical regions Ͻ cone .…”
mentioning
confidence: 99%
“…These characteristics as well as the entire neutral curves for both mϭ0 and mϭ1 are close to those for the Squire jet. 7 For example, Re a ϭ48.4, ϭ16.2, ␣ i ϭ0.323 at mϭ0 in the Squire jet.…”
mentioning
confidence: 99%